2017
DOI: 10.3390/rs9080769
|View full text |Cite
|
Sign up to set email alerts
|

On the Objectivity of the Objective Function—Problems with Unsupervised Segmentation Evaluation Based on Global Score and a Possible Remedy

Abstract: Abstract:Image segmentation is a crucial stage at the very beginning of many geographic object-based image analysis (GEOBIA) workflows. While segmentation quality is generally deemed of great importance, selecting adequate tuning parameters for a segmentation algorithm can be tedious and subjective. Procedures to automatically choose parameters of a segmentation algorithm are meant to make the process objective and reproducible. One of those approaches, and perhaps the most frequently used unsupervised paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
(46 reference statements)
0
31
0
Order By: Relevance
“…A multiresolution local variance strategy has inherent instability and depends on the spatial resolution of the imagery and the a priori knowledge. Segmentation evaluation metrics, such as a modification of the Global Score, should be tested with this method to make the segmentation reproducible and less subjective [60]. Third, it is well known that using multi-source data can improve crop classification accuracy, as different information can capture crop characteristics from alternative perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…A multiresolution local variance strategy has inherent instability and depends on the spatial resolution of the imagery and the a priori knowledge. Segmentation evaluation metrics, such as a modification of the Global Score, should be tested with this method to make the segmentation reproducible and less subjective [60]. Third, it is well known that using multi-source data can improve crop classification accuracy, as different information can capture crop characteristics from alternative perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research revealed that the overall goodness measure resulting from this USPO approach is highly dependent on the range of parameter considered during the optimization procedure 26 . Therefore, we performed some empirical tests to find parameters generating clearly over-segmented and under-segmented results.…”
Section: Segmentation and Unsupervised Segmentation Parameter Optimizmentioning
confidence: 99%
“…However, due to the normalization procedure, the values of GS and consequently, its optimum value, are sensitive to the range of candidate segmentations, as pointed out by Böck et al [31]. When the normalization of MI and WV is computed using the value of the finest and coarsest segmentations as minima and maxima (i.e., 0 and 1), a shift in these scales may also cause a shift in the optimum GS value.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for adequate results to be produced, the selection of an appropriate range of candidate segmentations might require substantial testing time to be found and moreover, still fall under the curse of subjectivity. In response, Böck et al [31] proposed to do the normalization using fixed minimum and maximum threshold values of MI and WV. In such manner, the optimal value identified by the GS would be the same regardless of the candidate segmentations considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation